O direito penal mínimo e a execução das penas alternativas na ótica dos direitos humanos - Oliveira, Helma Janielle Souza de (2009)
The scientific studies that take care of criminal measures have two punitive proposals for confronting violence: the Maximum criminal law theory and the theory of criminal law. The first expresses the intense criminalizing movement of social conducts and the punish stiffening, that results into an overcrowding of prisons and else confirms a interventionist State mode whose choice is the repressive treatment of the convicted instead of acting in a social ambit. Already the Minimum criminal law theory, together with the theory of Penal Garantism Theory, brings the proposal of reducing the punish character of State into the minimum required, and, thus, expect to cause the lowest suffering possible in the penalties application. That means just the exercising of the humans rights guarantee in favor of convicted, on the Brazilian penal execution, which enables its objective of replace that prisoner in social environment again. Considering the conditions of disrespect to human dignity, found in majority of Brazilian prisons establishments, the Minimum Penal Right tends to be applied through alternatives penalties to prison. Thus, the national penitentiary policy organization provides directions for the creation of institutions that takes care of alternatives penalties implementation like a solution to the inefficient prison system in Brazilian states, among them, the Supervision and Accompaniment of Penalties and Alternative Measures (CEFAPA), in Paraíba State. On the theme above, this work was developed through qualitative research, based on bibliographic and empirical studies, together with CEFAPA, to verify if the practice of alternative penal execution is less agressive of the human rights and achieves a garantist and appropriate answer to Minimum Penal Right. For both, visits were done in the Psychosocial Center of Paraíba State, situated on the judicial district of João Pessoa City, which allowed the realization of interviews with professionals and provides of alternative penalties. The results point difficulties of some providers related to the monitoring and understanding of the punish system because of the penalties easiness and their accidental causes. However, advantages were also verified, by displacing lawbreakers of minor or medium offensive potential from the ordinaries prisons environments; considering providers individualities; softening the prisoners stigmas and prejudices; enabling the reflection of the provider about his illicit conduct, reaching a social responsibility sense, without the incongruity of being out of his social group. Therewith, it is concluded that the alternatives penalties application is less aggressive of the humans rights, and therefore enables the lowest suffering to its recipients.